Modeling reservoir management for malaria control in Ethiopia - Kibret, Solomon (Sci Rep, 2019)
This study investigated how changes in reservoir water level affect mosquito abundance and malaria transmission in Ethiopia. Digital elevation models of three Ethiopian dams at lowland, midland and highland elevations were used to quantify water surface area and wetted shoreline at different reservoir water levels (70, 75, 80, 85, 90, 95 and 100% full capacity) to estimate surface area of potential mosquito breeding habitat. Reservoir water level drawdown rates of 10, 15 and 20 mm.day(−1) were applied as scenarios to model larval abundance, entomological inoculation rate (EIR) and malaria prevalence at each dam. Malaria treatment cost and economic cost in terms of lost working days were calculated for each water level scenario and dam. At the lowland dam, increased larval abundances were associated with increasing reservoir water level and wetted shoreline area. In contrast, both larval abundances and area of wetted shoreline declined with increasing reservoir water level at the midland and highland dams. Estimated EIR, malaria prevalence, malaria treatment cost and economic cost generally decreased when the water level drawdown rate increased from 10 to 15 and 20 mm.day(−1) irrespective of reservoir water level. Given the expansion of dam construction in sub-Saharan Africa, incorporating malaria control measures such as manipulating drawdown rates into reservoir management has the potential to reduce the malaria burden and health care costs in communities near reservoirs.